Molecular characterization of drug-resistant Mycobacterium tuberculosis among Filipino patients derived from the national tuberculosis prevalence survey Philippines 2016. (July 2022) - Montoya, Jaime C.; Malabad, John Carlo M.; Ang, Concepcion F.; Reyes, Lorenzo T.; Basilio, Ramon P.; Lim, Dodge R.; Amarillo, Maria Lourdes E.; Ama, Ma Cecilia G.; Phelan, Jody E.; Hibberd, Martin L.; Clark, Taane G.
Abstract: Tuberculosis, caused by Mycobacterium tuberculosis, remains a high burden disease and leading cause of mortality in the Philippines. Understanding the genetic diversity of M. tuberculosis strains in the population, including those that are multi-drug resistant (MDR), will aid in formulating strategies for effective TB control and prevention. By whole genome sequencing of M. tuberculosis isolates (n = 100) from patients of the Philippine 2016 National Tuberculosis Prevalence Survey, we sought to provide a baseline assessment of the genotypic and phylogenetic characteristics of the isolates. The majority (96/100) of the isolates were EAI2-Manila strain-type (lineage 1), with one Lineage 2 (Beijing), one Lineage 3 (CAS1), and two Lineage 4 (LAM9) strains. The EAI2-Manila clade was not significantly associated with patient's phenotypic and in silico drug resistance profile. Five (5/6) MDR-TB isolates predicted by in silico profiling were concordant with phenotypic drug resistance profile. Twenty-one mutations were identified in nine drug resistance-related genes, all of which have been reported in previous studies. Overall, the results from this study contribute to the growing data on the molecular characteristics of Philippine M. tuberculosis isolates, which can help in developing tools for rapid diagnosis of TB in the country, and thereby reducing the high burden of disease.